Chagas disease in southern Peru - Cornejo D., Alberto (1963)
Has completed extensive epidemiological, clinical , electrocardiographic and prophylactic regarding Chagas disease in the major population centers of two valleys of southern Peru , showing the presence of very favorable for the presence of this disease epidemiological factors . Almost 100% of households had T. infesfans and over 50% of them , these triatomines were infected with T. cruzi. Inside the homes of many and varied pets prevalent among guinea pigs, rabbits , cats and dogs , which have important role as a reservoir of T. cruzi are raised. 320 has been practiced xenodiagnoses to equal numbers of homes in Moquegua , resulting 12 positive among 113 dogs, 11 positive in 62 guinea pigs, 68 cats between 2 positive and 2 positive in 30 rabbits. The remaining (27 pigs , 8 horses , 6 goats, donkeys and 6 ) were negative. We practiced xenodiagnoses 752 and 553 reactions Guerreiro - Machado in a total of 771 residents of these valleys that were not previously selected , allowing the diagnosis of 105 new cases. It has been found that the symptoms and ECG abnormalities in these new cases are discrete ; Moreover, this poor symptoms and electrocardiographic signs were , paradoxically , more frequent in non- chagasic that chagasic . Cardiac involvement in 105 cases referred has not been frequent or had the characters of severity have been described elsewhere in America. We have investigated the effectiveness of Gamma -BHC - Cereclor against T. infestans population centers in the Moquegua Valley , yielding very encouraging results ten months after its implementation.